Whole-genome of Mexican-crAssphage isolated from the human gut microbiome - Melany Cervantes-Echeverría; Edgar Equihua-Medina; Fernanda Cornejo-Granados; Abigail Hernández-Reyna; Filiberto Sánchez; Blanca Estela López-Contreras; Samuel Canizales-Quinteros; Adrián Ochoa-Leyva (BMC Research Notes, 2018)
Abstract Objectives crAssphage is a newly found phage described as the most abundant virus in the human gut microbiome. The majority of the crAssphage proteins are unknown in sequences databases, and its pathogenicity and epidemiology in humans are yet unclear. Hence, being one of the most abundant phages in the human gut microbiome more investigation at the genomic level is necessary to improve our understanding, especially in the Latin American population. Data description In this article, we provide the whole genome of a crAssphage isolated from the human gut microbiome of the Mexican population, which was named Mexican-crAssphage. The genome consists of 96,283 bp, G+C content of 29.24% and 87 coding sequences. Notably, we did not find any transfer RNA genes in the genome sequence. We also sequenced viral-like enriched particles from 28 fecal samples, and we detected the presence of the Mexican-crAssphage genome in 8 samples (28.5%). To our knowledge, our data is the first whole genome report of the crAssphage isolated from the Latin American Population and provides valuable information for the experimental characterization of the most abundant human gut bacteriophage. The whole genome shotgun project of the Mexican-crAssphage is available at DDBJ/ENA/GenBank under the GenBank MK069403.